Исследование процесса термической переработки в солнечной печи отходов электродов из композита Mo—30% (мас.) Si - Пасичный, В.В.; Остапенко, С.А.; Пасичная, М.С.; Исаева, Л.П.; Тимофеева, И.И. (Электрические контакты и электроды, 2010)
Приведены методика и некоторые результаты термической переработки отходов электронагревателей из композиционного материала Mo—30% (мас.) Si при нагреве концентрированной солнечной энергией. Получено два основных вида продуктов переработки: нанодисперсная смесь конденсированных оксидов молибдена и кремния в соотношении около 3,5 : 1 (30,4% относительно унесенной массы материала) и различные по цвету, форме и структуре оплавленные продукты на основе оксидов кремния (около 50%). Приведено методику та деякі результати термічної переробки відходів електронагрівачів з композиційного матеріалу Mo—30% (мас.) Si при нагріві концентрованою сонячною енергією. Отримано два основних виду продуктів переробки: нанодисперсна суміш конденсованих оксидів молібдену і кремнію у співвідношенні близько 3,5 : 1 (30,4% відносно унесеної маси матеріалу) та різні по кольору, формі та структурі розплавлені продукти на основі оксидів кремнію. A search of untraditional energy and resource saving technologies of processing of waste is the topical task of materials researchers. A method and some results of the thermal processing of electric heaters of Mo—30% (mass.) Si composition at the concentrated solar energy heating are adduced. The solar furnace СГУ-1 with mirror concentrator ǿ 1,5 m was used for experiments. To obtain the condensed nanodispersive powders of metals oxides the heating was utilized up temperatures of melting and vaporization. The powders were accumulated in suction fabric trap. Two main types of products of processing are got: nano-dispersive mixture of condensed molybdenum and silicon oxides in correlation about 3,5:1 (30,4% in relation to the taken away mass of material) and different in color, of the form and structure melted products on the basis of silicon oxides (about 50%).